2015
DOI: 10.1002/art.39183
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Tumor Necrosis Factor and Interleukin‐6 Differentially Regulate Dkk‐1 in the Inflamed Arthritic Joint

Abstract: Objective Tumor necrosis factor (TNF) drives bone destruction, but it also inhibits new bone formation by inducing Dkk‐1, an inhibitor of the Wnt pathway. Accordingly, blocking of Dkk‐1 reverses the phenotype in experimental arthritis from a pattern of bone destruction to a pattern of bone formation. To delineate the potential role of Dkk‐1 in the structural phenotype of human arthritis, we analyzed the expression of Dkk‐1 and its regulation by proinflammatory cytokines in the inflamed peripheral joints of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 16 publications
1
32
0
Order By: Relevance
“…tis. An inverse correlation of DKK1 with IL-6 levels was also demonstrated in inflamed arthritic joints (Yeremenko et al, 2015). Previous studies have shown that DKK1 and SOST upregulated the expression of RANKL and downregulated that of OPG (Fujita & Janz, 2007;Wijenayaka et al, 2011).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…tis. An inverse correlation of DKK1 with IL-6 levels was also demonstrated in inflamed arthritic joints (Yeremenko et al, 2015). Previous studies have shown that DKK1 and SOST upregulated the expression of RANKL and downregulated that of OPG (Fujita & Janz, 2007;Wijenayaka et al, 2011).…”
Section: Discussionmentioning
confidence: 83%
“…These findings suggest that TNF‐α, IL‐1ß and IL‐6 might interact differently with the Wnt/β‐catenin antagonists in periodontitis. An inverse correlation of DKK1 with IL‐6 levels was also demonstrated in inflamed arthritic joints (Yeremenko et al., ). Previous studies have shown that DKK1 and SOST upregulated the expression of RANKL and downregulated that of OPG (Fujita & Janz, ; Wijenayaka et al., ).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These data implicate DKK-1 in inhibiting osteoblast-mediated bone formation in RA. Recently, IL-6 was shown to decrease DKK-1 levels in cultured fibroblast-like synoviocytes isolated from inflamed peripheral joints [80]. Thus, regulation of Wnt signaling may be a therapeutic approach to protection from bone loss in RA.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…In an effort to explore the strong link between Dkk-1 expression and the joint remodeling phenotype, Yeremenko and coworkers analyzed the expression of Dkk-1 and its regulation by proinflammatory cytokines in the inflamed peripheral joints of patients with SpA and RA. 28 178 Expression of Dkk-1 and proinflammatory cytokines were assessed in synovial fluid (SF) and synovial tissue while regulation of Dkk-1 production by proinflammatory cytokines was assessed in fibroblast-like synoviocyte (FLS) cultures. Dkk-1 circulating levels and DKK1 mRNA levels showed an inverse correlation with IL-6 levels in both SpA SF and RA SF.…”
Section: The Effect Of Proinflammatory Cytokines On Dkk-1 Expressionmentioning
confidence: 99%